Effect of CRABP1 expression on the proliferation and the sensitivity to retionoic acid of breast cancer cells of different origin - A. D. Enikeev; A. V. Komelkov; M. E. Axelrod; S. A. Galetsky; E. M. Tchevkina (Успехи молекулярной онкологии)
Background. Retinoic acid (RA), by modulation of the transcription of a number of retinoid-responsive genes, is involved in the regulation of cell differentiation and proliferation. The mechanisms by which the RA-binding proteins, molecular chaperones CRABP1 and CRABP2 (Cellular Retinoic Acid Proteins-1 and -2), participate in the realization of RA activity, as well as their precise role in tumor progression are still not fully understood. Recent data indicate that functional differences of CRABP proteins with respect to malignization of breast cancer cells could be determined by different sensitivity of tumor cells to RA and with the receptor status of the tumor.Materials and methods. The CRABP1 coding sequence was overexpressed in breast cancer cells without endogenous expression of this protein, with different levels of RA sensitivity and receptor status – SKBR3 (RA-sensitive, ER(–) / HER2(+) cells) and MDA-MB-231 (RA-resistant, triple negative status). The growth of CRABP1(+) derivatives and control cells was evaluated under standard culture conditions and in the presence of various concentrations of RA.Results. The effect of CRABP1 expression in RA-sensitive and RA-resistant breast cancer cells with different receptor status on the growth rate and sensitivity of cells to RA was studied. The expression of CRABP1 in RA-sensitive SKBR3 cells enhances proliferation in the absence of RA and decreases the antiproliferative effect of RA, while in RA-resistant triple-negative MDA-MB-231 cells, the expression of CRABP1 does not affect the studied characteristics.Conclusion. CRABP1 stimulates growth and suppresses the RA-sensitivity of HER2(+) RA-sensitive cells, but does not have a similar effect on highly aggressive triple-negative RA-resistant cells.